Effect of Short-term Use of Oral Contraceptive Pills on Intraocular Pressure - Rabail Alam, Tayyaba Gul Malik, Hina Nadeem Eiman Ayesha (Pakistan Journal of Ophthalmology, 2019)
Purpose: To study the effect of short-term use of oral contraceptive pills on intra-ocular pressures of women of childbearing age. Study Design: Observational case control study. Place and Duration of Study: The study was conducted at Arif memorial teaching hospital and Allied hospital Faisalabad from October 2017 to March 2018. Material and Methods: There were 100 female subjects, who were divided into two groups of 50 each. Group A, included females, who had been taking oral contraceptive pills (OCP) for more than 6 months and less than 36 months. Group B, included 50 age-matched controls, who had never used OCP. Ophthalmic and systemic history was taken. Careful Slit lamp examination was performed and intraocular pressures (IOP) were measured using Goldman Applanation tonometer. Fundus examination was done to rule out any posterior segment disease. We compared the intra ocular pressures between the two groups by using Student t test. Results: Average age was 29.16 in group A and 27.74 years in group B. Average duration of using OCP was 14.9 months. Mean IOP in right eye was 13.08 ? 1.41 mm of Hg and 13.34 ? 1.27 mm of Hg in left eye in Group A. While, mean IOP in right eye was 11.72 ? 1.35 mm of Hg and in left eye was 11.92 ? 1.3 mm of Hg in controls. Significant difference was noted between the IOP of OCP group and controls. (p = 0.000). Conclusion: OCP significantly increases IOP even when used for short time period. Key words: Oral contraceptive pills, Intra-ocular pressure, Glaucoma.